Efektifitas Terapi Murottal Al-Qur’an terhadap Intensitas Nyeri pada Pasien Pascaoperasi Ortopedi - Salma, Salma; Tanjung, Dudut; Tanjung, Riswani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effectiveness of mutual Al-Qur'an therapy on pain intensity in post-orthopedic surgery patients. This research method is Quasi experiment pre-post non-equivalent with a control group. The sample of this study were long bone ORIF postoperative patients totaling 37 in the control group and 37 in the experimental group. Data collection was carried out twice pre and post murottal intervention with the Brief Pain Inventory (BPI) instrument. Data analysis used Mann-Whitney statistical test analysis. The results showed that the p-value was 0.000 (α <0.05) which indicated that Ha was accepted or murottal Al-Qur'an therapy was effective in reducing pain intensity in post-orthopedic surgery patients at dr. Fauziah Bireuen. In conclusion, Al-Qur'an murotal therapy can be applied as an intervention in providing nursing care to post-ORIF patients to reduce pain levels. Keywords: Al-Qur'an Murottal Therapy, Pain Intensity, Postoperative Orthopedic.